Academic procrastination of medical students: The role of Internet addiction - HAYAT, ALI ASGHAR (J Adv Med Educ Prof, 2020)
INTRODUCTION: The internet is an essential and widely used tool for college students; however, high internet dependency can have negative consequences for students, especially regarding academic careers. Such students may tend to postpone their academic tasks. Hence, the current study examines the effect of Internet addiction on academic procrastination among medical students. METHODS: We applied a cross-sectional correlational research design. 233 medical students of Shiraz University of Medical Sciences were selected through convenience sampling and participated in this study. To collect the data, we used two valid and reliable questionnaires. The first was Young's Internet addiction questionnaire (IAT-20), which consists of 20 items based on a 5-point Likert-type scale. The second was Solomon and Rothblum academic procrastination questionnaire, which consists of 18 items based on a 5 point Likert-type scale. We used Pearson correlation, independent T-test, and One-Way ANOVA to analyze the data in SPSS version 22, and considered a significance level of p < 0.05. RESULTS: Results showed that 57.1% of the respondents were females, and the remaining were males. Findings indicated that 8 (3.43%) of the participants were classiﬁed as severe internet-addicted, and 28.85% of them had a high level of academic procrastination. The results indicated that there was a positive and significant correlation between Internet addiction and academic procrastination (r=0.39, with p<0.01). Also, there was a positive correlation between academic procrastination dimensions (writing a term paper, studying for an exam, keeping up with weekly reading assignments, performing administrative tasks, attending meetings and performing academic tasks in general) and Internet addiction (r=0.22, r=0.32, r=0.21, r=0.29, r=0.33, and r=0.23, respectively, with p<0.01). Finally, the results revealed that male students and those living in the dormitory had a higher level of Internet addiction and procrastination compared to female ones and those living at home (p<0.01). CONCLUSION: The findings of the current research reveal that a considerable number of students have levels of Internet addiction and procrastination; the study highlights that students with high levels of Internet addiction are more likely to be at an increased risk of negative outcomes such as insufﬁciently controlled Internet use.